Avicenna on abstraction - Translate: asif ihsani (حکمت اسرا)
The theory of abstraction is one of the most puzzling parts ofAvicenna's philosophy. What Avicenna says in many passages about thehuman intellect's capacity to derive universal knowledge from sense-dataseems to plainly contradict passages in the same works about the emanationof knowledge from the active intellect, a separately existing substance.When he maintains that "considering the particulars [stored inimagination] disposes the soul for something abstracted to flow upon itfrom the active intellect", 1 he appears to combine two incompatible conceptsin one doctrine: either the intelligible forms emanate from above orthey are abstracted from the data collected by the senses, but not both.